2022
DOI: 10.1159/000526472
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Delivery Is Associated with Neurochemical Evidence of Increased Neuroaxonal Remodelling in Infants from the KUNO-Kids Health Study: Cross-Sectional Analysis

Abstract: <b><i>Aim:</i></b> Little is known about neonatal brain plasticity or the impact of birth mode on neurointegrity. As a reflection of neuroaxonal damage, the neuronal structural protein neurofilament light chain (NfL) has emerged as a highly specific biomarker. Our purpose was to test the hypothesis that vaginal delivery is associated with increased NfL in neonates. <b><i>Methods:</i></b> NfL concentrations were measured using single-molecule array immunoassay in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Shah et al found that NfL cutoff levels associated with adverse neurodevelopmental outcomes increased from 28 pg/ml at 18 h after perinatal HI to 436 pg/ml at 98 h after HI (18). Time after birth alone may also have an effect; Depoorter et al showed that NfL plasma concentrations in healthy preterm and term infants increase after birth from 18.2 pg/ml in umbilical cord blood to 50.9 pg/ml on day 3 (5) which is in part related to delivery mode (6) and might in addition be related to transition from the intra-uterine environment to extra-uterine life. To explore a possible contribution in our model of time after birth without HI, we analysed serum samples from four control piglets not subjected to HIE, but to anaesthesia and mechanical ventilation only.…”
Section: Temporal Profile Of Nfl After Hypoxiaischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Shah et al found that NfL cutoff levels associated with adverse neurodevelopmental outcomes increased from 28 pg/ml at 18 h after perinatal HI to 436 pg/ml at 98 h after HI (18). Time after birth alone may also have an effect; Depoorter et al showed that NfL plasma concentrations in healthy preterm and term infants increase after birth from 18.2 pg/ml in umbilical cord blood to 50.9 pg/ml on day 3 (5) which is in part related to delivery mode (6) and might in addition be related to transition from the intra-uterine environment to extra-uterine life. To explore a possible contribution in our model of time after birth without HI, we analysed serum samples from four control piglets not subjected to HIE, but to anaesthesia and mechanical ventilation only.…”
Section: Temporal Profile Of Nfl After Hypoxiaischemiamentioning
confidence: 99%
“…NfL levels increase with acute or chronic neuronal injury, including stroke and traumatic brain injury in adults ( 4 ). NfL can be measured in newborns and has been found to be higher after vaginal delivery than after caesarean section and further increased in newborns suffering from intraventricular haemorrhage ( 5 , 6 ). Clinical interpretation of NfL in HIE is challenged by competing aetiologies of neonatal encephalopathy and uncertain timing of hypoxic-ischemic events.…”
Section: Introductionmentioning
confidence: 99%